Planning for Enhanced Waste Separation to Optimize Urban Waste Recycling at Recycling Facilities - Mubaroq, Ahmad Zakhi; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Journal of Sustainable Infrastructure, 2024)
The escalating challenge of waste management in the context of increasing urbanization and changing consumption patterns has accentuated the need for effective waste separation and recycling practices. This research investigates the intricate waste separation processes within recycling facilities, specifically focusing on optimizing plastic waste recycling. Waste separation plays a pivotal role in resource recovery and minimizing environmental impact. Plastic waste, characterized by diverse polymer types and forms, requires specialized separation techniques. The primary objective of this study is to analyze the potential for waste separation within a recycling facility and to propose optimization strategies for plastic waste recycling. By comprehensively assessing the waste separation processes, this research aims to identify challenges, bottlenecks, and opportunities for innovation. Insights derived from data-driven analysis will guide the formulation of targeted optimization approaches, contributing to the transition towards a circular economy and sustainable waste management practices.